2018
DOI: 10.1017/s0031182018000306
|View full text |Cite
|
Sign up to set email alerts
|

Infection patterns and molecular data reveal host and tissue specificity ofPosthodiplostomumspecies in centrarchid hosts

Abstract: Posthodiplostomum minimum utilizes a three-host life cycle with multiple developmental stages. The metacercarial stage, commonly known as 'white grub', infects the visceral organs of many freshwater fishes and was historically considered a host generalist due to its limited morphological variation among a wide range of hosts. In this study, infection data and molecular techniques were used to evaluate the host and tissue specificity of Posthodiplostomum metacercariae in centrarchid fishes. Eleven centrarchid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 49 publications
0
31
0
1
Order By: Relevance
“…Lane et al (2015) recorded ''white grub'' P. minimum metacercariae in many fish species. Boone et al (2018) detected white grub (P. minimum) metacercariae in the visceral organs of many centrarchids freshwater fishes. Kvach et al (2017) detected Posthodiplostomum cf.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lane et al (2015) recorded ''white grub'' P. minimum metacercariae in many fish species. Boone et al (2018) detected white grub (P. minimum) metacercariae in the visceral organs of many centrarchids freshwater fishes. Kvach et al (2017) detected Posthodiplostomum cf.…”
Section: Discussionmentioning
confidence: 99%
“…distinctly bipartite body and tribocytic organ was discshaped with a median slit) and showed well-developed gonads and anlagen of some genital organs, but no melanin. (Boone et al 2018) mentioned that P. minimum metacercariae has limited morphological variation among a wide range of hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as seen above, morphometric deviations relative to these studies were small, and Palmieri (1977) showed that adult morphology varies a great deal within P. centrarchi. Also, deviations were obtained from hologenophores genetically matching P. centrarchi common in centrarchid hosts (e.g., see records in (Boone et al, 2018;Locke et al, 2010)), and therefore there is no doubt they represent P. centrarchi.…”
Section: Remarksmentioning
confidence: 99%
“…Hoffman (1958Hoffman ( , 1999 considered P. centrarchi a subspecies of P. minimum and named it P. minimum centrarchi because he proved that it could infect only centrarchid fishes while P. minimum minimum was able to infect only cyprinids. The strict host specificity of the P. minimum subspecies was supported by Locke et al (2010a,b), Lane et al (2015), Stoyanov et al (2017a) and Boone et al (2018). Accordingly, Stoyanov et al (2017a) elevated P. minimum centrarchi to species rank as P. centrarchi, and this novel name has become general since then (Kvach et al, 2018a;Ondra ckov a et al, 2019).…”
Section: Introductionmentioning
confidence: 86%